Annals of General Psychiatry - Fountoulakis, Konstantinos N.; Pompili, Maurizio; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Annals of General Psychiatry considers manuscripts on all aspects of psychiatry, including neuroscience and psychological medicine. Both basic and clinical neuroscience contributions are encouraged. Annals of General Psychiatry emphasizes a biopsychosocial approach to illness and health and strongly supports and follows the principles of evidence-based medicine. As an open access journal, Annals of General Psychiatry facilitates the worldwide distribution of high quality psychiatry and mental health research. The journal considers submissions on a wide range of topics including, but not limited to, psychopharmacology, forensic psychiatry, psychotic disorders, psychiatric genetics, and mood and anxiety disorders.
Keywords: Psychiatry; Psychopharmacology; Forensic psychiatry; Geriatric psychiatry; Psychotherapy; Psychiatry; Psychopharmacology; Forensic Psychiatry; Geriatric Psychiatry; Psychotherapy